Cathepsin B regulates non‐canonical NLRP3 inflammasome pathway by modulating activation of caspase‐11 in Kupffer cells. (7th August 2018) - Chen, Nan; Ou, Zhibing; Zhang, Wenfeng; Zhu, Xiwen; Li, Peizhi; Gong, Jianping
Abstract: Objectives: The non‐canonical inflammasome pathway was described which engages caspase‐11 to mediate pyroptosis and the subsequent release of IL‐1α, IL‐1β and IL‐18 in TLR4‐independent way. Cathepsin B is capable of activating caspase‐11 under cell‐free conditions which may regulate non‐canonical NLRP3 inflammasome pathway. In this study, we aimed to further investigate cathepsin B as potential activators of proinflammatory caspases which may be released upon proinflammatory stimuli and regulate non‐canonical NLRP3 inflammasome pathway by modulating the activity of caspase‐11. Methods: Pharmacological and gene‐silencing approaches were used to evaluate the impact of cathepsin B on regulating non‐canonical NLRP3 inflammasome pathway in wild‐type and TLR4 –/– Kupffer cells. A sepsis model was also created to investigate the effect of cathepsin B on survival. Meanwhile, cathepsin B activity and the expression level of caspase‐4 were detected in human peripheral blood mononuclear cells (PBMC) which were separated from patients suffered from SIRS or sepsis and healthy volunteers. Results: LPS stimulation caused cathepsin B activity and caspase‐11 expression increase in TLR4 –/– mice. Cathepsin B activity inhibition reduced the activation of caspase‐11 and inflammasome and benefited survival in TLR4 –/– mice. Upregulation of cathepsin B activity and caspase‐4 activation was found in PBMC of patients with SIRS or sepsis. Conclusion: Our results suggest a critical role for cathepsin B as activators of proinflammatory caspases‐11 and the regulatory effect in LPS‐induced caspases‐11‐dependent necrosis.